Hepatoprotective Effects of Apple Cider Vinegar on Gentamicin Induced Toxicity in Albino Rats (Medical Forum Monthly, 2022)
Objective: To assess the morphological effects of Apple cider vinegar on hepatotoxicity caused by gentamicin in male adult albino rats.Study Design: Experimental study.Place and Duration of Study: This study was conducted at the Department of Anatomy, Postgraduate Medical Institute (PGMI), Lahore, Pakistan for a period of 21 days starting on June 1st, 2019.Materials and Methods: This experimental study comprised 30 male adult albino rats divided into three groups, A, B and C with 10 rats in each group. Group A was control and it received distilled water 4ml/kg/day via intra-peritoneal route for 21 days. Group B received only Gentamicin 100mg/kg/day from day 10th-21st intraperitoneally. Groups C received Apple cider vinegar 2ml/kg/day via oral gavage for first 10 days then along with Gentamicin 100mg/kg/day intraperitoneally for next 11 days upto day 21st. Rats were sacrificed on 22nd day. Histological parameters of liver i.e., size of hepatocyte, hepatocyte vacuolization and central vein congestion were studied. The results were analyzed by SPSS version 22.0.Results: Hepatocyte size in group B was significantly higher when compared with group A and C (p value < 0.001). However, no significant difference was observed in the hepatocyte size between the group A and C. Hepatocyte vacuolization was absent in all rats of control group A but present in all rats of group B. While it was present in 3 rats (30%) of group C. No rat of group A showed congested central vein but all rats of group B showed congested central vein. Only 1 rat (10%) of group C showed congestion of central vein of liver.Conclusion: From the foregoing results, it is clear that gentamicin can induce many histological changes in the liver causing severe toxicity that is reflected in the parameters i.e., size of hepatocyte, central vein congestion and hepatocyte vacuolization. It also demonstrates that apple cider vinegar protects against its hepatotoxicity on molecular level through its antioxidants pathways.